2016
DOI: 10.19082/2551
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Factors Influencing on Total Fertility Rate in Iran: A Panel Data Analysis for the Period of 2002-2012

Abstract: IntroductionOver the last few decades, total fertility rate (TFR) has followed a downward trend in Iran. The consequences of this trend from the perspectives of some are negative. Considering the macro-population policies in recent years, this study aimed to examine the effect of some macro socio-economic variables, including divorce, marriage, urbanization, and unemployment rate on TFR in Iran from 2002 to 2012.MethodsThis time series research was conducted in 2015 using the databases of the National Organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…In 2016, the per capita service fee varied from 45.00- Table 2 The provincial variation of the variables from 2009 to 2016 Variable 2009 2010 2011 2012 2013 2014 2015 2016 MMR 7.02-232. 23 It was observed in this study that the maternal health service utilization was associated with the deduction in the MMR after other healthcare resource covariates were adjusted. As described above, previous studies had demonstrated the negative correlation between antenatal care [7,30] or postpartum care [31,32] and maternal mortality, but rarely were there any studies focused on the relationship between maternal mortality and maternal health management from the antenatal to postpartum period.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In 2016, the per capita service fee varied from 45.00- Table 2 The provincial variation of the variables from 2009 to 2016 Variable 2009 2010 2011 2012 2013 2014 2015 2016 MMR 7.02-232. 23 It was observed in this study that the maternal health service utilization was associated with the deduction in the MMR after other healthcare resource covariates were adjusted. As described above, previous studies had demonstrated the negative correlation between antenatal care [7,30] or postpartum care [31,32] and maternal mortality, but rarely were there any studies focused on the relationship between maternal mortality and maternal health management from the antenatal to postpartum period.…”
Section: Discussionmentioning
confidence: 64%
“…In addition, the statistical methods used in the previous studies were mostly univariate correlation analyses [20] or linear regressions [21], which may not be effective enough to adjust the time-invariant in the longitudinal data. Panel data models, on the other hand, could be more suitable to analyze the cross-sectional samples with multiple time points [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…This is not the first study to examine the correlated of the number of children ever born and its spatial variation. A number of other studies have used children ever born as a dependent variable (Jafari et al, 2016, Kabir, Jahan, Shahidul, and Ali, 2001, Sharma 2015, Lindstrom, Gebre-Egziabher, and Hogan, 2009. Figure 3 shows the maximum number (not the average) of children reported in a cluster (y-axis) and the cumulative number of clusters reporting that maximum (x-axis).…”
Section: The Dependent Variable: Cluster Average Of the Number Of Chimentioning
confidence: 99%
“…Iran is one of the developing countries that has experienced a sharp decline in fertility worldwide. [ 1 ] This declining trend has been such that the total fertility rate has decreased from 6.3 in 1986[ 2 ] to 1.98 in 2000 and in 2018 it has reached 1.62. [ 3 ] According to the results of the last census in 2016, among the provinces of Iran, Hamedan, located in the West of Iran, with a population growth rate of −0.23, had the lowest population growth rate in Iran.…”
Section: Introductionmentioning
confidence: 99%